2019
DOI: 10.1038/s41598-019-46925-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening older adults for amnestic mild cognitive impairment and early-stage Alzheimer’s disease using upper-extremity dual-tasking

Abstract: The purpose of the current study was to develop an objective tool based on dual-task performance for screening early-stage Alzheimer’s disease (AD) and mild cognitive impairment (MCI of the Alzheimer’s type). Dual-task involved a simultaneous execution of a sensor-based upper-extremity function (UEF) motor task (normal or rapid speed) and a cognitive task of counting numbers backward (by ones or threes). Motor function speed and variability were recorded and compared between cognitive groups using ANOVAs, adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 51 publications
(62 reference statements)
2
44
0
Order By: Relevance
“…The diagnostic potential of keystroke dynamics has been proven in previous studies (52) and our results of longer, more variant pressing of the keyboard keys and slower finger coordination across the screen for the MCI patients, further strengthens this potential. These findings are also aligned with studies experimenting with finger tapping speed (24), associated with short-memory lapses and other fine motor dexterity (53) and upper extremity function (21) tests conducted in a clinical setting (data in-the-clinic). Nevertheless, our approach goes several steps further by encapsulating the natural state of the users, capturing non-invasively and longitudinally their typing sessions, without the need for special technical equipment and during their pragmatic real-life activities (data in-the-wild), thus enabling a continuous monitoring of the very early stages of the condition.…”
Section: Discussionsupporting
confidence: 75%
“…The diagnostic potential of keystroke dynamics has been proven in previous studies (52) and our results of longer, more variant pressing of the keyboard keys and slower finger coordination across the screen for the MCI patients, further strengthens this potential. These findings are also aligned with studies experimenting with finger tapping speed (24), associated with short-memory lapses and other fine motor dexterity (53) and upper extremity function (21) tests conducted in a clinical setting (data in-the-clinic). Nevertheless, our approach goes several steps further by encapsulating the natural state of the users, capturing non-invasively and longitudinally their typing sessions, without the need for special technical equipment and during their pragmatic real-life activities (data in-the-wild), thus enabling a continuous monitoring of the very early stages of the condition.…”
Section: Discussionsupporting
confidence: 75%
“…Despite the potential methodological concerns in relating grip strength to cognition, it is noted that other motor tasks may be of value, particularly since coordination of the upper extremity may be sensitive to cognitive ageing 26,27 . Upper extremity tasks that involve functional movement likely rely on more cognitive processes than maximal force production, which recruits primarily sensorimotor cortical regions.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly UEF [see Toosizadeh et al (2019) and Ehsani et al (2019)], seems to be a promising techniques.…”
Section: Barriers and Opportunitiesmentioning
confidence: 99%
“…The authors reported that the UEF task owns sensitivity and specificity of 0.82 and 0.72 respectively; therefore it may become a rapid tool for cognitive screening. The ratio underlying the research is that muscle strength, reflexive performance, and dynamic balance deficits could excessively influence the ability of walking, whereas elbow flexion is a less musculoskeletal demanding task, which may be more suitable for cognitive assessment [Toosizadeh et al (2019)]. J o u r n a l P r e -p r o o f DT walking: -counting backwards by 7.…”
mentioning
confidence: 99%